Forecasting Final Energy Consumption using the Centered Moving Average Method and Time Series Analysis - Janina POPEANGA; Ion LUNGU (Database Systems Journal, 2014)
The forecasting of energy consumption has become one of the major fields of research in recent years. Accurate energy demand forecasting is essential in energy system operations and planning. In this paper, we will describe a method to determine the information that is useful for a good forecasting. Further, we adopt the time series modeling approach to model final energy consumption in Romania using previous data of 2010 to 2013. This method is implemented using stored procedures, developed in Oracle PL/SQL programming language. Finally, the developed model is compared for goodness of fit to the historical data and forecasting accuracy, and results are encouraging, showing that the forecast model is in control and is working correctly.